Modelling of strip buckling in the continuous annealing process. (26th November 2017) - Bai, Z. H.; Wang, R.; Du, J. C.; Wang, Y. X.; Liu, Y. X.; Cui, Y. Y.; Qian, C.; Li, B. Y.
Abstract : This paper considers the equipment and technological characteristics of continuous annealing process (CAP) to solve the issue of strip buckling. It analyses the mechanism of hot buckling and transverse compressive stresses from internal and external forces. A basic description of strip buckling is given together with a new concept of a buckling index. The critical buckling condition is presented, and the model of strip buckling index in the CAP is proposed. The distribution of strip buckling index in different sections of the process is analysed quantitatively along with the influence of incoming strip shape, transverse temperature difference, roller profile, friction coefficient, set tension and strip processing speed on the strip hot buckling index in CAP. Results show that with the influence of thermal stress, the transverse compressive stress that affects the middle part of the strip is largest in the heating section, which is also where hot buckling occurs most easily; centripetal force is dominant in the soaking and slow cooling sections, and in these sections buckling occurs at the roller shoulder. In different sections, the strip buckling index distribution differs, whereas the influence of other parameters on buckling index remains similar.